Unmaking migrants : Nigeria's campaign to end human trafficking - Vanderhurst, Stacey (Police/worlds., 2022)
"An ethnographic account of Nigeria's campaign to stop human trafficking and migration into sex work, told from inside a rehabilitation center for trafficked women" --